MANAJEMEN HUBUNGAN MASYARAKAT (HUMAS) DAN PEMASARAN RS PKU MUHAMMADIYAH YOGYAKARTA - Annisa Fitriani (International Journal of Healthcare Research, 2019)
Public Relations of PKU Muhammadiyah Hospital Yogyakarta has an important role in improving the quality of services at PKU Muhammadiyah Hospital Yogyakarta. That will make public believe that PKU Muhammadiyah Hospital Yogyakarta has good quality health services that can maintain customer relationships, and increased profit at PKU Muhammadiyah Hospital Yogyakarta. Purpose: This study aims to knowing general overview of Public Relations and Marketing at PKU Muhammadiyah Hospital Yogyakarta. Methods: This research is qualitative research with observation and interview method for data collection in Public Relations and Marketing at PKU Muhammadiyah Hospital Yogyakarta. Results: Based on the results, public relations management and marketing of PKU Muhammadiyah Yogyakarta Hospital is implemented by planning, organizing, actuating, controlling and evaluating. The marketing mix is doing on product, price, promotion, and place. Conclusion: Hospital marketing mix activities have been doing well and there needs to be additional people, process and physical evidence elements to improve the marketing and image of the Hospital.